(untitled) (Journal of Informatics Education and Research, 2026)
The “human in the loop” (HIL) label that currently exists has become an exaggerated umbrella over critical distinctions within human–AI partnerships. This will provide a tripartite schema that categorises the HIL (AI led, automation first), AI in the loop (AI2L; human led, augmentation first) and Hybrid Intelligence/Collaborative Intelligence (HI/CI; co creative partnership). We suggest a paradigm–domain correspondence: efficiency driven contexts favor HIL, accountability driven domains favor AI2L, and creativity driven domains favor HI/CI. We integrate evidence to support a continuing agency–performance tradeoff in high stakes environments, the AI identification challenge, and the homogenization risk of scaled generative models on culture. We suggest for move from a brittle “human in the loop” backstop to participatory governance — organized, multi-stakeholder overview of the entire lifecycle. A four-part research agenda and a maturity model of human involvement are provided to inform empirical validation and ethical deployment. This analysis lays the groundwork for more sophisticated analyses and calls for interdisciplinary, field based evaluation of human–AI systems to ensure they augment human flourishing in ways consistent with the principle of preserving diversity of thought and autonomy of judgement.